Analisis Perencaan Peningkatan Kualitas Mutu Lulusan di Sekolah - Arizul Suwar (Tadabbur: Jurnal Peradaban Islam, 2022)
Planning to improve the quality of graduates is the obligation of educational institutions, especially schools as an effort to realize the ideals of national education. Improving the quality of graduates in schools is usually carried out through the policy of the school principal who acts as a leader who mobilizes the school community to realize the school's vision, mission, goals and objectives through programs that are implemented in a planned and gradual manner. The goal to be achieved from quality improvement planning is produce quality graduates to prepare graduates to face their future. The preparation of quality improvement plans in schools is usually carried out in two stages, namely: preparation of a work program and preparation of a curriculum. This article aims to analyze plans to improve the quality of graduates along with their derivative discussions carried out by schools. This study uses library research methods. The findings of this article are that planning to improve the quality of graduates in schools is still oriented towards quantity and has not yet touched the quality dimension. The quality of graduates is only measured through numbers such as report cards, test scores, and the number of students who pass. The dimensions of quality as mandated in the law such as creative, responsible, independent and so on must also be considered. With regard to the increasingly high demands and competition in the world of work, this cannot be answered without solid personality qualities. One of the main personality qualities is creativity.